The Braze of Bela in Pushkin's Novel - Usmanova Dilfuza Rakhmatullaevna (Genius Publishing Group, 2024)
In this article we examined the image of the main character of Pushkin’s novel. This is the daughter of a prince, a young Circassian woman. We learn about her in the first part of the novel, which bears the same name. Daughter of the mountains Bela... We meet this heroine from the very first pages of the novel. In the novel we see Bela as pure, kind and sincere. In Bel, Pechorin immediately notices the integrity and naturalness of nature.
Keywords: Tenderness; ardor; captive; feeling